SANTA CLAUS SOLIDARITY FOR PALESTINE: A SEMIOTIC ANALYSIS OF THE MOHAMMAD TOROKMAN’S PHOTOJOURNALISM - Novan Jemmi Andrea (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2020)
Mohammad Torokman is a photojournalist with the Reuters News Agency. Torokman's photojournalism is chosen as